Rural-urban residence and emergency contraception use, access, and counseling in the United States, 2006-2017 - Carly M. Milkowski; Erika C. Ziller; Katherine A. Ahrens (Elsevier, 2021)
Objective: To estimate differences in emergency contraception (EC) use, access, and counseling by rural-urban residence among reproductive age women in the United States. Study design: We examined respondent data (2006-2017) from the National Survey of Family Growth for women ages 15-44 (n = 28,448) to estimate EC use, access, and counseling by rural-urban county of residence. Rural-urban prevalence ratios for EC outcome measures were estimated using predicted margins from logistic regression models, which were adjusted for demographic differences and current contraceptive method use. Changes in ever-use of EC over time were estimated for rural and urban respondents, separately, using Chi-square tests and trends were estimated using inverse variance weighted linear regression models. Results: During 2006 to 2017, 10% of rural and 19% of urban women who had ever had sex reported ever using EC pills. Among rural women, ever-use increased from 6% in 2006-2008 to 15% in 2015-2017 (Chi-square p < 0.01; trend p-value < 0.01); among urban women, ever-use increased from 11% to 27% (Chi-square p < 0.01; trend p-value < 0.01). Rural and urban women were similarly likely to have obtained EC without a prescription and from a drug store. Rural women were less likely to have received EC counseling than urban women; however, counseling rates were low among all women. Conclusion: We observed differences in EC ever-use and receipt of EC counseling by rural-urban residence among US women ages 15 to 44, adding to the evidence that rural-urban residence is an important factor in reproductive health. More research is needed to explore factors contributing to rural-urban differences in EC use. Implications: Our key finding that EC use varied by rural-urban county residence offers additional evidence that rural-urban residence should be considered in reproductive health practice and policy. We discuss areas for future research into potential barriers to EC use in rural populations.